Supply Chain Risk Management: A Field Study on the Poultry Industry of Bangladesh (Global Journal of Management and Business Research, 2024)
Supply chain risk management (SCRM.) has become a subject of significant interest in academic and business circles in today's highly competitive business environment. The purpose of the study is to investigate the risks associated with the poultry sector in Bangladesh and mitigation strategies. This study utilizes qualitative field studies and interviews to explore risk factors and mitigation strategies in Bangladesh's poultry industry, guided by a systematic review. Financial, technical, human resources, policy, and nature are among the main identified risks. To decrease chances and strengthen the resilience of the supply chain, respondents propose that improved technology, insurance, human resources management, disease control, transport, support from governments, or feeds should be considered. This paper proposes a theoretical framework and practical risk mitigation methods, addressing sustainability challenges and aiming to support the industry and associated livelihoods in Bangladesh.
Keywords: bangladesh; poultry industry; supply chain management; supply chain risk management